Correlates of continuum of maternal health services among Nepalese women: Evidence from Nepal Multiple Indicator Cluster Survey. - Binaya Chalise (PLoS ONE, 2019)
Continuum of Care (CoC) is an essential strategy to prevent maternal and child deaths where health services are arranged in a pathway throughout pregnancy, childbirth and after delivery. However, CoC is still a challenge in Nepal. This study aimed to investigate the correlates of CoC from pregnancy to the postnatal period in Nepalese women aged 15 to 49 years. Secondary analysis was performed on the data from Nepal Multiple Indicator Cluster Survey. This led to a sample size of 2086 women who had a live birth within two years preceding the survey. We constructed three outcome models and conducted multivariable logistic regression, to assess socio-economic and demographic correlates of CoC from pregnancy to childbirth to postnatal period. Overall, 41% of the women received Antenatal Care (ANC), delivery from Skilled Birth Attendant (SBA) as well as the Postnatal Care (PNC) during their most recent birth. Women from rural areas (aOR 0.25, 95%CI: 0.18, 0.36) had reduced odds of receiving CoC while women belonging to advantaged ethnic group (aOR 1.61, 95%CI: 1.18 2.19), from middle wealth status (aOR 2.56, 95%CI: 1.68, 3.91) and upper (aOR 4.50, 95%CI: 3.07, 6.59) wealth status, and women having access to media (aOR 1.76, 95%CI: 1.31, 2.37) had higher odds of receiving CoC from pregnancy to postnatal period. Having more than two births reduced the odds of CoC by 30% (aOR 0.70, 95%CI: 0.50, 0.98). These factors were also significantly associated with ANC services and the continuum from ANC to delivery SBA. The findings suggest that the majority of Nepalese women lack a continuity of care during their pregnancy and childbirth, and several socioeconomic factors affect the spectrum of CoC. Efforts to improve maternal health services utilization in a continuum require strategies that remove demand and supply barriers of health care utilization.